2011
DOI: 10.1111/j.1755-0238.2011.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Guaiacol and 4-methylguaiacol accumulate in wines made from smoke-affected fruit because of hydrolysis of their conjugates

Abstract: Background and Aims: Taint in smoke-exposed grapes have been associated with elevated levels of guaiacol and 4-methylguaiacol. Previous research has reported guaiacol and 4-methylguaiacol in both fruits and wines. In some cases, these compounds were not detected, or were detected at low levels in the fruit while high levels were subsequently identified during or after winemaking. Later research indicated that this was due to the presence of glycosidic conjugates. Here we report a method for the routine analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 25 publications
3
77
0
Order By: Relevance
“…However, it can be observed that wines from treatments had lower pH values than control wine, meaning that treatments improved the microbiological stability of wines. On the other hand, wines from G treatment had the lowest alcoholic degree, which could be related with the negative effect in the sugar accumulation of grapes observed by Kennison, Wilkinson, Pollnitz, Williams, and Gibberd (2009) which studied grapevine exposure, being the guaiacol a component of the smoke and present at elevated concentration in wines from smoke-affected grapes (Singh et al, 2011). Anyway, G treatment seems to affect the primary metabolism of the plant because the wines obtained had also less acidity than wines from the other treatments.…”
Section: Oenological Parametersmentioning
confidence: 91%
See 1 more Smart Citation
“…However, it can be observed that wines from treatments had lower pH values than control wine, meaning that treatments improved the microbiological stability of wines. On the other hand, wines from G treatment had the lowest alcoholic degree, which could be related with the negative effect in the sugar accumulation of grapes observed by Kennison, Wilkinson, Pollnitz, Williams, and Gibberd (2009) which studied grapevine exposure, being the guaiacol a component of the smoke and present at elevated concentration in wines from smoke-affected grapes (Singh et al, 2011). Anyway, G treatment seems to affect the primary metabolism of the plant because the wines obtained had also less acidity than wines from the other treatments.…”
Section: Oenological Parametersmentioning
confidence: 91%
“…The aroma glycosidic precursors are a diverse group of odorless compounds which can suffer hydrolysis by acids or enzymes, giving the odour-active aglycones (Gunata, Bayonove, Baumes, & Cordonnier, 1985). An increase of glycosylated forms of guaiacol and 4-methylguaiacol were observed when grapevines were exposed to smoke from the fire forests (Singh et al, 2011). On the other hand, when both volatiles were applied together, higher volatile concentration of each compound was produced in wines than when they were applied independently.…”
Section: Eugenol and Guaiacol By Sbse-gc-msmentioning
confidence: 98%
“…However, glycosylated precursors may also be present in the flesh of severely exposed grapes (Singh et al, 2011), and even the free-run juice of smoke-tainted grapes can contain high levels of 4-MG and guaiacol (Kennison et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of burning fynbos, and the sensory properties of the smoke produced, have not yet been assessed in any context. Investigations in Australia have established that wine produced from grapes exposed to smoke from bushfires develop objectionable smoky, ashy and burnt characters (Kennison et al, 2008;Sheppard et al, 2009;Hayasaka et al, 2010;Singh et al, 2011). Guaiacol and 4-methylguaiacol (4-MG) have been used as key indicators of smoke exposure and potential taint formation (Kennison et al, 2007;Sheppard et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation